Estimation of total fertility rate and birth averted due to contraception: regression approach - Devkota, Bijaya Mani (Nepal Population Journal, 2018)
Fertility plays an important role in any demographic transition and total fertility rate (TFR) is one of the basic measurements of fertility. Absences of complete and reliable data, a large number of indirect techniques have been developed to estimate the demographic parameters with incomplete data. Some of these techniques are based on utilizing the data from stable population theory while others are based on the regression technique in which the parameters are estimated through regression equations between the dependent variable which is the TFR and the independent variables which is the socio economic well as demographic variables. The first method is based on the relationship between the Total fertility rate (TFR) and contraceptive prevalence rate for all women. By using this modified estimate of TFR, demographic analysis can easily calculate the birth averted for different regions as well as states also. In fact, provide reasonable estimates of births averted due to contraceptive use by national populations. The variables are CPR that about 51.2 percent variation in TFR can be explained by the first regression approach. The second is based on the relationship between total fertility rate (TFR) and Additive combination of CPR and proportion of currently married females having open birth interval. Using new predictor variable, the improved model explained about 55percent of the variation in TFR. The findings reveal that the values of TFR calculated by the present method are quite close to the observed values of the TFR without involving much computational complexities at different background characteristics. Estimates of births averted and the percent change in births in the absence of contraception, based on the two methods, are fairly consistent.